Tanggung Gugat Terhadap Penyalahgunaan Hak Guna Usaha pada Lahan Perkebunan - Rachman Maulana Kafrawi; Bambang Ariyanto; Nikmah Mentari (Jurnal Hukum IUS QUIA IUSTUM, 2022)
Misperceptions or misconceptions on the importance of land in people's lives by turning land into an economic commodity have triggered social conflicts, one of the most prominent problems in the land sector lately is social conflict over plantation land. The problems studied in this research are how is the mechanism for the permit of Cultivation Rights (Hak Guna Usaha, HGU) on plantation land and how to hold accountability for the use of plantation land outside the Cultivation Right. The method used is normative juridical by using normative analysis methods. The results of this study conclude that land misuse often occurs because of overlapping land ownership and the acquisition of the land has not been completed in the granting of the Cultivation Rights. Holders of Cultivation Rights often ignore their obligations, causing disputes that are detrimental to other parties. So that the holder of the Cultivation Right is responsible for everything he does that causes harm to other parties. Key Words: Accountability; abuse; cultivation rights; plantation land Abstrak Pemahaman atau persepsi yang keliru terhadap arti pentingnya tanah dalam kehidupan masyarakat dengan memanfaatkan tanah sebagai komoditi ekonomi semata, telah memicu konflik sosial, salah satu permasalahan di bidang pertanahan yang menonjol akhir-akhir ini adalah konflik sosial di atas tanah perkebunan. Permasalahan yang akan dikaji ialah mengenai bagaimana mekanisme izin Hak Guna Usaha (HGU) atas lahan perkebunan serta bagaimana tanggung gugat atas penggunaan lahan perkebunan diluar Hak Guna Usaha. Metode penelitian yang digunakan yuridis normatif dengan menggunakan metode analisis normatif. Hasil dari penelitian ini menyimpulkan penyalahgunaan tanah sering terjadi karena adanya tumpang tindih kepemilikan tanah juga pembebasan/perolehan tanah belum tuntas dalam pemberian Hak Guna Usaha. Pemegang Hak Guna Usaha seringkali menghiraukan kewajiban-kewajibannya sehingga menimbulkan sengketa yang merugikan pihak lain. Sehingga pemegang Hak Guna Usaha tersebut bertanggung gugat atas segala hal yang dilakukannya yang menimbulkan kerugian bagi pihak lain. Kata-kata Kunci: Tanggung gugat; penyalahgunaan; hak guna usaha; lahan perkebunan